Postmortem morphology of honeybee stings induced fatal anaphylaxis - Grusova, Katerina; Vojtisek, Tomas; Tse, Rexson; Kalinka, Tomas (International journal of legal medicine, 2025)
Despite numerous case reports in the literature, high-quality postmortem images of honeybee sting are scant in postmortem literature. We report a case of a fatal anaphylactic death from honeybee stings with detailed high-quality annotated macroscopic and microscopic morphological images. A woman in her mid-60's was found dead in her garden cabin unexpectedly after mowing the lawn near her beehives in late evening hours. She passed away despite resuscitation efforts. External examination showed multiple honeybee stings on the body. A number of them had a nidus near the center in which a stinger was confirmed by subsequent histology. Postmortem examination and ancillary testing showed features of anaphylaxis.
Keywords: Anaphylaxis; Animals; Female; anafylaxe; ženské pohlaví; lidé; kousnutí a bodnutí hmyzem; Honey bee; Insect Bites and Stings; Forensic pathology; Insect; fatální výsledek; Fatal Outcome; Postmortem; Bees; včely; lidé středního věku; Autopsy; zvířata; Middle Aged; Humans